2018
DOI: 10.5121/ijaia.2018.9503
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Innovation of an Information Communication System and Upgrade of the Knowledge Base in Industry by ESB, Artificial Intelligence, and Big Data System Integration

Abstract: In this paper, a case study is analyzed. This case study is about an upgrade of an industry communication system developed by following Frascati research guidelines. The knowledge Base (KB) of the industry is gained by means of different tools that are able to provide data and information having different formats and structures into an unique bus system connected to a Big Data. The initial part of the research is focused on the implementation of strategic tools, which can able to upgrade the KB. The second par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
1
6
0
1
Order By: Relevance
“…The clustering analysis carried out by the k-means algorithms allows to suggest to the agent the products to be proposed to the customer based on his characteristics. It is observed that the LSTM approach is suitable for augmented and artificial data [25]. This validates the choice to use the LSTM tools for the specific case study.…”
Section: Resultssupporting
confidence: 61%
“…The clustering analysis carried out by the k-means algorithms allows to suggest to the agent the products to be proposed to the customer based on his characteristics. It is observed that the LSTM approach is suitable for augmented and artificial data [25]. This validates the choice to use the LSTM tools for the specific case study.…”
Section: Resultssupporting
confidence: 61%
“…The goal of the proposed paper is the study of motion detection sensitivity results of a prototype video surveillance system # RNN Model construction model = Sequential() model.add (SimpleRNN(units=128, input_shape=(1, step), activation="relu", return_sequences=True)) model.add (SimpleRNN(units=64, activation="relu", return_sequences=True)) model.add (SimpleRNN(units=64, activation="relu") figure(figsize=(20,12) figure(figsize=(20,12) Below is illustrated a screenshot proving the correct implementation of the tables of the prototype platform. (3,9) * t[i]) number_of_late_deliveries = int(0.1 * random.randrange(0, 8) * np.cos(0.003 * random.randrange (1,8) * t[i]) + 0.5 * random.randrange(0, 1) * np.cos( 0.001 * random.randrange (3,8) * t[i])) velocita_chiusura_trattativa = 0.1 * random.randrange(0, 1) * np.sin(0.004 * random.randrange (5,9) (3,4) * t[i]) percentuale_incassato = 0.1 * random.randrange(0, 5) * np.cos(0.008 * random.randrange (2,9) * t[i]) + 0.3 * random.randrange(0, 2) * np.sin( 0.001 * random.randrange (3,9)…”
Section: Appendix A: Neural Network Algorithmsmentioning
confidence: 99%
“…* t[i]) + 0.1 * random.randrange(0, 2) * np.cos( 0.001 * random.randrange(3,6) * t[i]) attivita_completate_trattativa = int(0.1 * random.randrange(0, 9) * np.cos(0.007 * random.randrange(1, 7) * t[i]) + 0.8 * random.randrange(0, 3) * np.cos( 0.001 * random.randrange(3, 5) * t[i])) ratio_attivita_settore_completate_totale_attivita_completate = 0.1 * random.randrange(0, 3) * np.tan(0.009 * random.randrange(2, 7) * t[i]) + 0.7 * random.randrange(0, 4) * np.tan( 0.001 * random.randrange(3, 4) * t[i]) ratio_attivita_settore_non_completate_totale_attivita_non_completate = 0.1 * random.randrange(0, 4) * np.cos(0.006 * random.randrange(1, 8) * t[i]) + 0.2 * random.randrange(0, 8) * np.tan( 0.001 * random.randrange(3, 7) * t[i]) valutazione_rischio = 0.1 * random.randrange(0, 2) * np.sin(0.008 * random.randrange(2, 9) * t[i]) + 0.4 * random.randrange(0, 9) * np.cos( 0.001 * random.randrange(3, 4) * t[i]) referenze_acquisite = int(0.1 * random.randrange(0, 3) * np.cos(0.002 * random.randrange(5, 8) * t[i]) + 0.6 * random.randrange(0, 4) * np.sin( 0.001 * random.randrange(3, 9) * t[i])) variabilita_servizi_venduti = int(0.1 * random.randrange(0, 7) * np.sin(0.001 * random.randrange(1, 2) * t[i]) + 0.5 * random.randrange(0, 6) * np.sin( 0.001 * random.randrange(3, 8) * t[i])) order_processing_time = 0.1 * random.randrange(0, 6) * np.sin(0.003 * random.randrange(2, 3) * t[i]) + 0.4 * random.randrange(0, 3) * np.cos( 0.001 * random.randrange…”
mentioning
confidence: 99%
“…So, the software and licenses used in research projects (indicated in Fig. 2 by SW) therefore become essential elements for structuring a knowledge base from which to implement an advanced BI necessary for the revisitation and the innovation of processes and services [27].…”
Section: Development Of the Project Specifications By Following Frascmentioning
confidence: 99%